EFEKTIVITAS IPCR UNI EROPA DALAM MENGATASI KRISIS PANDEMI COVID-19 TAHUN 2020 - Shella Apriani; de Fretes, Christian Herman Johan (Department of International Relations Universitas Satya Negara Indonesia, 2023)
This article aims to analyze the effectiveness of the European Union in overcoming the 2020 COVID-19 pandemic crisis, with a case study of the Integrated Political Crisis Response (IPCR) policy in place. This article uses a qualitative research method, namely literature study to answer the research question of this article. Arild Underdal's regime effectiveness approach was then used to analyze the effectiveness of the EU in responding to the crisis caused by the COVID-19 pandemic through the IPCR policy, using three variables, namely dependent, independent, and regime effectiveness. This study explains that the EU's IPCR policy was not effective enough to overcome the COVID- 19 crisis in 2020 because it was faced with the national policies of member countries. Their policies posed challenges to the coordination and integration of the EU. The increase in the number of COVID-19 cases was also a new challenge in the mechanism offered by the IPCR because all member countries imposed regional restriction policies.